2019
DOI: 10.1177/1063426619884271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cross-Age Tutors With EBD for Kindergarteners At Risk of Mathematics Difficulties

Abstract: Challenges with numerical proficiency at an early age can lead to substantial gaps in learning and are associated with detrimental long-term outcomes. In addition, students with emotional–behavioral disorders (EBD) can have some of the most challenging behavioral and academic needs to address. The purpose of this study was to identify the effects and collateral outcomes of utilizing cross-age tutors (i.e., older students) with/at risk of EBD to deliver a number line board game intervention to kindergarten stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Students, teachers, and parents of students participating in CAT-EBD programs have reported high levels of perceived effectiveness and a strong desire to continue the program once it ends (Watts et al, 2020). The CAT-EBD model helps to utilize the limited resources in a school/classroom to maximize differentiation in instruction, increases the availability for special educators to provide direct instruction to students with the most intensive needs, and deepens the quality of authentic social-emotional-behavioral skills practice and acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Students, teachers, and parents of students participating in CAT-EBD programs have reported high levels of perceived effectiveness and a strong desire to continue the program once it ends (Watts et al, 2020). The CAT-EBD model helps to utilize the limited resources in a school/classroom to maximize differentiation in instruction, increases the availability for special educators to provide direct instruction to students with the most intensive needs, and deepens the quality of authentic social-emotional-behavioral skills practice and acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…A simple invitation to these stakeholders to come observe a tutoring session can increase opportunities for praise for the participating students from new sources, therefore increasing engagement, confidence, and pride in their new skills. These invitations can prove to be beneficial for the observers, who may be surprised in seeing familiar students with EBD exhibit unfamiliar, positive social-behavioral skills (i.e., changing their own perspectives/expectations of the students' abilities; Watts et al, 2020).…”
Section: Planning and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is not surprising that both researchers and practitioners have called for more work to address the needs of students with co-occurring RD and inattention during small group reading instruction, as well as to address student engagement through improved instructional practices (Kauffman, 2010; Lemons et al, 2016; MacDonald et al, 2021; Roberts et al, 2021, 2023). Additionally, researchers have found that educators not only need a behavior support program to be effective, but also one that is easy to understand (i.e., usable), perceived to be effective, and able to be implemented with fidelity (i.e., feasible) (Kuchle & Riley-Tillman, 2019; Lawson et al, 2023; Lemons et al, 2016; Watts et al, 2019; 2020). Overall, the identification of such a usable, feasible, and effective behavior support program that can be integrated into small group reading instruction is timely and necessary to support schools in delivering effective interventions for students with RD+Inattention (e.g., Eisman et al, 2020; Kauffman 2010; Lemons et al, 2016; Ringwalt et al, 2016; Roberts et al, 2020; 2021).…”
mentioning
confidence: 99%